2006
DOI: 10.4049/jimmunol.177.5.2880
|View full text |Cite
|
Sign up to set email alerts
|

Primitive Lymphoid Progenitors in Bone Marrow with T Lineage Reconstituting Potential

Abstract: Multiple subsets of the bone marrow contain T cell precursors, but it remains unclear which is most likely to replenish the adult thymus. Therefore, RAG-1+ early lymphoid progenitors (RAG-1+ ELP), and CD62L/L-selectin+ progenitors (LSP), as well as common lymphoid progenitors from C57BL6-Thy1.1-RAG-1/GFP mouse bone marrow were directly compared in transplantation assays. The two c-Kithigh populations vigorously regenerated the thymus and were superior to common lymphoid progenitors in magnitude and frequency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
1
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 57 publications
6
65
1
1
Order By: Relevance
“…had accelerated T lineage kinetics but generated fewer peak progeny for a shorter period of time than MPP (Fig. 2, A and C), as expected from past work with irradiated recipient mice (14,40,47,54). Interestingly, although CLP are phenotypically c-Kit low , they up-regulated c-Kit to generate c-Kit high ETP and DN2 thymocytes by day 8 after transfer.…”
Section: Selectivity Of Thymus Settlingsupporting
confidence: 59%
See 1 more Smart Citation
“…had accelerated T lineage kinetics but generated fewer peak progeny for a shorter period of time than MPP (Fig. 2, A and C), as expected from past work with irradiated recipient mice (14,40,47,54). Interestingly, although CLP are phenotypically c-Kit low , they up-regulated c-Kit to generate c-Kit high ETP and DN2 thymocytes by day 8 after transfer.…”
Section: Selectivity Of Thymus Settlingsupporting
confidence: 59%
“…We were unable to find CLP in the bloodstream of adult mice (18). However, a new study suggests that low numbers of CLP-like cells may circulate (54). Therefore, CLP may directly contribute to T cell development, although they are much less efficient T lineage progenitors than MPP.…”
Section: Discussionmentioning
confidence: 69%
“…Consistent with this model, we reported previously that the Flk2 + subset of CLPs has robust T-cell potential (Karsunky et al 2008), and that it is the predominant source of T cells within the bone marrow in transplantation experiments . However, other studies have suggested that CLPs predominantly differentiate into B cells, and that a population upstream of CLPs, the multipotent progenitor (MPP, sometimes called LMPP [lymphoid-primed MPP]), is the major source of T-cell progenitors from the bone marrow (Schwarz and Bhandoola 2004;Perry et al 2006;Lai and Kondo 2007;Wada et al 2008). These contradictory findings may have resulted from B-cell-biased progenitors that copurify and contaminate preparations of CLPs.…”
mentioning
confidence: 99%
“…The LMPP, the ELP and the CLP are detectable in peripheral blood, whereas the CLP-2 has not been found in the blood (Schwarz and Bhandoola, 2004;Perry et al, 2006;Krueger and von Boehmer, 2007;Umland et al, 2007). Recently, a novel T-lineage-committed progenitor subset presumably downstream of the CLP-2 was found in adult murine blood.…”
Section: Developmental Pathways In Murine Hematopoiesismentioning
confidence: 99%